2022
DOI: 10.1186/s12943-022-01494-z
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear function for an oncogenic microRNA as a modulator of snRNA and splicing

Abstract: Background miRNAs are regulatory transcripts established as repressors of mRNA stability and translation that have been functionally implicated in carcinogenesis. miR-10b is one of the key onco-miRs associated with multiple forms of cancer. Malignant gliomas exhibit particularly striking dependence on miR-10b. However, despite the therapeutic potential of miR-10b targeting, this miRNA’s poorly investigated and largely unconventional properties hamper the clinical translation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 98 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…In silico analysis of PGK1 and IGFBP2 mRNAs identified both canonical (seed-containing) and non-canonical miR-10b-binding sites in the PGK1 and IGFBP2 3′ UTRs and additional sites in the IGFBP2 ORF and 5′ UTR ( Table S1 ). 20 As miR-10b has an established non-canonical binding activity, 7 , 21 we considered multiple putative binding sites and tested them for the direct binding and regulation by miR-10b using PGK1 and IGFBP2 fragments subcloned into psiCheck2 luciferase reporter vectors. Two reporters have been constructed for PGK1 and four reporters for IGFBP2 (corresponding to three alternative mRNA variants and their shared sequence).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico analysis of PGK1 and IGFBP2 mRNAs identified both canonical (seed-containing) and non-canonical miR-10b-binding sites in the PGK1 and IGFBP2 3′ UTRs and additional sites in the IGFBP2 ORF and 5′ UTR ( Table S1 ). 20 As miR-10b has an established non-canonical binding activity, 7 , 21 we considered multiple putative binding sites and tested them for the direct binding and regulation by miR-10b using PGK1 and IGFBP2 fragments subcloned into psiCheck2 luciferase reporter vectors. Two reporters have been constructed for PGK1 and four reporters for IGFBP2 (corresponding to three alternative mRNA variants and their shared sequence).…”
Section: Resultsmentioning
confidence: 99%
“…However, the mechanisms mediating the effects of both PGK1 and IGFBP2 on GSCs require further investigation. Of note, the incomplete rescue provided by PGK1 and IGFBP2 inhibitors, as well as established functions of miR-10b in controlling diverse signaling pathways in glioma, 5 , 6 , 7 , 10 , 21 , 50 suggest that additional factors released by miR-10b-edited cells may contribute to the observed bystander mechanism. Overall, our findings demonstrate that miR-10b editing reduces the growth of glioma cells in both autonomous and non-autonomous ways, further supporting its potential for GBM therapy development.…”
Section: Discussionmentioning
confidence: 99%
“…SnRNA can also regulate the occurrence of cancer. For example, U6snRNA is a key component of spliceosome RNA and the primary target of miR-10b in glioblastoma, which can regulate its development [132]. SnoRNA can compete with U11snRNA RNP, thereby altering the splicing of mRNA encoding E2F transcription factor (E2F7), which can lead to head and neck cancer and retinal cancer [51].…”
Section: Other Ncrna and Cancermentioning
confidence: 99%
“…Recent studies revealed that approximately 351 miRNAs are dysregulated in GBM (68), and some of them have been associated with acquired malignant phenotypes such as tumor growth, proliferation, invasion, and angiogenesis. Among others, miRNA-21, miRNA-10b, miRNA-7, miRNA-100, miRNA-296, miRNA-210-3p, miRNA-128, and miRNA-221 are the prominent candidates that have been studied and investigated for miRNA-based therapeutic strategies in GBM (68)(69)(70)(71)(72). Alongside miRNAs, long ncRNAs (lncRNAs) have also been observed to control many cellular processes in glioma cells predominantly associated with GBM and its malignancy (68,73,74).…”
Section: Epigenetic Landscape and Non-coding Rnas In Gbmsmentioning
confidence: 99%